Estimating IBNR claim reserves using Gaussian Fuzzy Numbers - Bastos, Ismael Sampaio; Vana, Leonardo Bruno; Novo, Carolina Cardoso (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The study aimed to propose a new approach to the chain-ladder method using for that Gaussian Fuzzy Numbers. For that, the text introduces concepts and establishes new perspectives that allow not just the use of this kind of fuzzy number in the claim estimation context but also in other areas of knowledge, corroborating, in that way, to the expansion of the adoption of fuzzy logics in a general sense. The results indicates that the adoption of the proposed method offers huge benefits when compared to the traditional approach and previous works exploring other kind of fuzzy numbers. Keywords: claim reserves; fuzzy logic; fuzzy numbers; IBNR.